Auditory cortex asymmetry, altered minicolumn spacing and absence of ageing effects in schizophrenia. - Chance, SA; Casanova, M; Switala, A; Crow, T (2008)
The superior temporal gyrus, which contains the auditory cortex, including the planum temporale, is the most consistently altered neocortical structure in schizophrenia (Shenton ME, Dickey CC, Frumin M, McCarley RW. A review of MRI findings in schizophrenia. Schizophr Res 2001; 49: 1-52). Auditory hallucinations are associated with abnormalities in this region and activation in Heschl's gyrus. Our review of 34 MRI and 5 post-mortem studies of planum temporale reveals that half of those measuring region size reported a change in schizophrenia, usually consistent with a reduction in the left hemisphere and a relative increase in the right hemisphere. Furthermore, female subjects are under-represented in the literature and insight from sex differences may be lost. Here we present evidence from post-mortem brain (N = 21 patients, compared with 17 previously reported controls) that normal age-associated changes in planum temporale are not found in schizophrenia. These age-associated differences are reported in an adult population (age range 29-90 years) and were not found in the primary auditory cortex of Heschl's gyrus, indicating that they are selective to the more plastic regions of association cortex involved in cognition. Areas and volumes of Heschl's gyrus and planum temporale and the separation of the minicolumns that are held to be the structural units of the cerebral cortex were assessed in patients. Minicolumn distribution in planum temporale and Heschl's gyrus was assessed on Nissl-stained sections by semi-automated microscope image analysis. The cortical surface area of planum temporale in the left hemisphere (usually asymmetrically larger) was positively correlated with its constituent minicolumn spacing in patients and controls. Surface area asymmetry of planum temporale was reduced in patients with schizophrenia by a reduction in the left hemisphere (F = 7.7, df 1,32, P < 0.01). The relationship between cortical asymmetry and the connecting, interhemispheric callosal white matter was also investigated; minicolumn asymmetry of both Heschl's gyrus and planum temporale was correlated with axon number in the wrong subregions of the corpus callosum in patients. The spacing of minicolumns was altered in a sex-dependent manner due to the absence of age-related minicolumn thinning in schizophrenia. This is interpreted as a failure of adult neuroplasticity that maintains neuropil space. The arrested capacity to absorb anomalous events and cognitive demands may confer vulnerability to schizophrenic symptoms when adult neuroplastic demands are not met.